A plausible link between the asteroid 21 Lutetia and CH carbonaceous chondrites. (October 2016) - Moyano‐Cambero, Carles E.; Trigo‐Rodrίguez, Josep M.; Llorca, Jordi; Fornasier, Sonia; Barucci, Maria A.; Rimola, Albert
Abstract: A crucial topic in planetology research is establishing links between primitive meteorites and their parent asteroids. In this study, we investigate the feasibility of a connection between asteroids similar to 21 Lutetia, encountered by the Rosetta mission in July 2010, and the CH3 carbonaceous chondrite Pecora Escarpment 91467 (PCA 91467). Several spectra of this meteorite were acquired in the ultraviolet to near‐infrared (0.3–2.2 μm) and in the midinfrared to thermal infrared (2.5–30.0 μm or 4000 to ~333 cm −1 ), and they are compared here to spectra from the asteroid 21 Lutetia. There are several similarities in absorption bands and overall spectral behavior between this CH3 meteorite and 21 Lutetia. Considering also that the bulk density of Lutetia is similar to that of CH chondrites, we suggest that this asteroid could be similar, or related to, the parent body of these meteorites, if not the parent body itself. However, the apparent surface diversity of Lutetia pointed out in previous studies indicates that it could simultaneously be related to other types of chondrites. Future discovery of additional unweathered CH chondrites could provide deeper insight in the possible connection between this family of metal‐rich carbonaceous chondrites and 21 Lutetia or other featureless, possibly hydrated high‐albedo asteroids.